(untitled) (International Journal of Computer Science and Engineering, 2026)
While conventional wastewater remediation literature extensively documents single-pollutant removal, the intricate interfacial interactions governing the simultaneous sequestration of heavy metals and organic dyes within complex co-contaminated matrices remain largely unresolved due to oversimplified experimental designs in prior studies. To address these limitations, a modified biomass-based adsorbent was engineered, though achieving optimal surface functionalization required rigorous methodological adjustments to overcome initial structural instabilities encountered during the chemical cross-linking phase. Batch equilibrium experiments elucidated distinct competitive behaviors; the presence of anionic dyes to some extent suppressed heavy metal uptake, a phenomenon likely driven by steric site-blocking effects or potential electronic repulsion, though alternate explanations involving synergistic molecular chelating pathways cannot be entirely discounted. Considering these competing dynamics, multi-component isotherm models were applied, revealing that the spatial redistribution of active functional groups is highly dependent on initial solute concentration ratios. This research elevates the theoretical understanding of multi-solute interfacial chemistry beyond empirical observations, highlighting how engineered biomass can be strategically tailored for real-world textile effluents, although further research is needed to fully evaluate its long-term economic and structural viability under continuous-flow conditions.